Experimental study on characteristics of water containing coal complex resistivity dispersion. (November 2018) - Lei, Dongji; Zhao, Chenguang; Zhang, Yugui; Liu, Su
Abstract: In recent years, there have been great advances in the evaluation of complex resistivity method for rock permeability. Using a complex resistivity method, as a potential non-contact detection method, it is feasible to forecast the permeability of coal seam and evaluate the effect of hydraulic fracturing. In this paper, measurement and numerical simulation are both carried out based on electrical properties of rock. For this purpose, the authors attempted to measure real and imaginary parts of the complex resistivity of two kinds of metamorphic coal in different values of water saturation ( Sw ) under normal temperature and pressure conditions. The achieved experimental results are presented as follows: (1) The influence of polarization on the complex resistance is very important, which is the cause of frequency dispersion; (2) Regarding real and imaginary parts of the complex resistivity of coal's dispersion characteristics, the real part always gradually decreases with the increase of frequency, while the imaginary part is changed, and the curve has obvious extreme point; (3) the amplitude of real and imaginary parts gradually decrease with increase of Sw ; (4) The curve of imaginary part is two segments(only peak), the Cole-Cole model is applicable, while curve is three segments (trough-peak), the double Cole-Cole model is applicable. The results show that the effect of medium polarizability on coal complex resistivity cannot be ignored, indicating that complex resistivity method possesses a great capability in terms of development of coalbed methane and coal mining. Highlights: Revealing the dispersion characteristics of complex resistivity of containing water coal. Expounding the mechanism of dispersion of coal, microcosmic are interface polarization, orientation polarization, ion polarization; Low frequency is the induced polarization, high frequency is electromagnetic induction. Applying the Cole-Cole model to coal. When the imaginary part has only a wave peak, the Cole-Cole model is applicable, and when the curve is the trough-wave peak, utilizing the double Cole-Cole model is appropriate.